The strategy of stores localization - Cempírek, Václav; Kampf, Rudolf (Univerzita Pardubice, 2007)
This article is published as the part of research of the GAČR project ,,Outsourcing in transport – logistic processes“. The article deals with problematic of stores space localization. Choice of optimal object localization is concerned in almost all places in distribution logistics, where are produced and stored products, raw materials and semi-finished products. So it concerns space localization of main factoring concerns, raw materials stores, products stores, wholesales (distribution and logistics centers) and retail network in attachment on places of final consumption.
Strategie rozmístění skladů
Keywords: sklady; prostorová lokalizace; strategie rozmístění; logistické řetězce